Zinc oxide eugenol and Endoflas pulpectomy in primary molars: 24-month clinical and radiographic evaluation - Jayalakshmi Pandranki; Narsimha Rao V Vanga; Srinivas Kumar Chandrabhatla (Wolters Kluwer Medknow Publications, 2018)
Context: Despite modern advancement in material and technical aspect, management of infected primary molars is of prime concern in pediatric endodontics. An effective root canal material plays the major role in achieving the fluid impervious seal by defending against variant microflora and maintaining the tooth in function for longer duration. Aims: This study aims to evaluate and compare the success of endoflas as root canal filling material in infected primary molars with zinc oxide eugenol (ZOE). Materials and Methods: Primary molars with necrotic pulp in healthy, cooperative children were selected. Ethical clearance and informed consent was obtained. Standardized pulpectomy procedure was done and root canals were filled with either ZOE or endoflas. Further follow-up with clinical and radiographic evaluation was carried at 0, 3, 6, 12, and 24 months. The findings obtained were statistically analyzed using Chi-square test. Results: Endoflas showed acceptable results as root canal filling material in primary molars even at 2-year follow-up, though overfilling of root canals led to low success rate compared to teeth with combined optimal and under fillings. There was no significant difference between the two materials (P > 0.05). Conclusions: Endoflas could be a potential alternative to ZOE for preserving infected primary molars.